Climate Change Shrinks and Fragments Salmon Habitats in a Snow‐Dependent Region - Daniele Tonina; James A. McKean; Daniel Isaak; Rohan M. Benjankar; Chunling Tang; Qiuwen Chen (Geophysical Research Letters)
Abstract Climate change threatens biodiversity through global alteration of habitats, but efficient conservation responses are often hindered by imprecise downscaling of impacts. Besides thermal effects, warming also drives important ancillary environmental changes, such as when river hydrology evolves in response to climate forcing. Earlier snowmelt runoff and summer flow declines are broadly manifested in snow‐dependent regions and relevant to socioeconomically important cold‐water fishes. Here, we mechanistically quantify how climate‐induced summer flow declines during historical and future periods cause complex local changes in Chinook salmon (Oncorhynchus tshawytscha) habitats for juveniles and spawning adults. Changes consisted of large reductions in useable habitat area and connectivity between the main channel and adjacent off‐channel habitats. These reductions decrease the capacity of freshwater habitats to support historical salmon abundances and could pose risks to population persistence in some areas.